Integrated Digital Nudge in Gamification for Public Transportation Applications - Dyah Wahyu Sukmaningsih; Edi Abdurachman; Agung Trisetyarso; Betty Purwandari (Information)
A shift from private to mass transportation is one of the main goals of many governments. In this context, integrating digital nudges into gamification on digital platforms is a promising approach to influencing and changing user behavior. This study emphasizes the importance of understanding user needs and design requirements in developing effective solutions. A mixed-methods approach combined user interviews, expert interviews, thematic analysis, HEXAD questionnaires, and gamification workshops to collect and analyze needs. These methods comprehensively understand user expectations, gamification elements, and appropriate digital nudges. Based on these findings, a prototype was developed, which was then evaluated through a preliminary evaluation in the form of usability testing using questionnaires and interviews. The study results indicate that the design of digital nudges in the context of gamification can be effectively applied to public transportation applications and can potentially change user behavior in a more positive direction.